DESCRIPTION OF SURGICAL CARE IN UKRAINE IN 2005-2014: NATIONAL AND REGIONAL ASPECTS - Донік, О.М. (World of Medicine and Biology, 2016)
The treatment of patients with the congenital and acquired heart disease, coronary heart disease or its difficult rhythm disturbance could not be possible without surgical intervention. In this research of analysis of cardiac surgery aid dynamics in Ukraine during 2005–2014s was using the official medical statistics data. The main attention is paid to the operative heart intervention frequency and postsurgical lethality on the national and regional levels. The increase of volumes of cardiac surgery aid is set for indicated period in 3,5 times more. Moreover, the specific weight of cardiac surgery among all operative interventions grew up from 0,3% to 1,16%. The analysis of regional features of cardiac surgery aid displayed the most frequency operative heart interventions in Kyiv and Dnipropetrovsk region (22,42 and 12,17 surgeries on a 10 thousand of population accordingly), the most low – in Chernivtsi and Sumy region (0,12 and 0,49 on 10 thousand of population). The correlation analysis conducted on all regions of Ukraine detected the weak back coupling between the cardiac surgery frequency and postsurgical lethality.
Keywords: cardiac surgery aid; cardiovascular surgeons; cardiac surgeries; postsurgical lethality